Green Emissive Copper(I) Coordination Polymer Supported by the Diethylpyridylphosphine Ligand as a Luminescent Sensor for Overheating Processes - Enikeeva, Kamila R.; Shamsieva, Aliia V.; Strelnik, Anna G.; Fayzullin, Robert R.; Zakharychev, Dmitry V.; Kolesnikov, Ilya E.; Dayanova, Irina R.; Gerasimova, Tatiana P.; Strelnik, Igor D.; Musina, Elvira I.; Karasik, Andrey A.; Sinyashin, Oleg G. (Molecules (Basel, Switzerland), 2023)
Tertiary diethylpyridylphosphine was synthesized by the reaction of pyridylphosphine with bromoethane in a suberbasic medium. The reaction of phosphine with the copper(I) iodide led to the formation of a copper(I) coordination polymer, which, according to the X-ray diffraction data, has an intermediate structure with a copper-halide core between the octahedral and stairstep geometries of the Cu4I4 clusters. The obtained coordination polymer exhibits a green emission in the solid state, which is caused by the 3(M+X)LCT transitions. The heating up of the copper(I) coordination polymer to 138.5 °C results in its monomerization and the formation of a new solid-state phase. The new phase exhibits a red emission, with the emission band maximum at 725 nm. According to the experimental data and quantum chemical computations, it was concluded that depolymerization probably leads to a complex that is formed with the octahedral structure of the copper-halide core. The resulting solid-state phase can be backward-converted to the polymer phase via recrystallization from the acetone or DMF. Therefore, the obtained coordination polymer can be considered a sensor or detector for the overheating of processes that should be maintained at temperatures below 138 °C (e.g., engines, boiling liquids, solar heat systems, etc.).